Dependability Engineering - Pedro García Márquez, Fausto; Papaelias, Mayorkinos (IntechOpen, 2018)
The new technology and system communication advances are being employed in any system, being more complex. The system dependability considers the technical complexity, size, and interdependency of the system. The stochastic characteristic together with the complexity of the systems as dependability requires to be under control the Reliability, Availability, Maintainability, and Safety (RAMS). The dependability contemplates, therefore, the faults/failures, downtimes, stoppages, worker errors, etc. Dependability also refers to emergent properties, i.e., properties generated indirectly from other systems by the system analyzed. Dependability, understood as general description of system performance, requires advanced analytics that are considered in this book. Dependability management and engineering are covered with case studies and best practices. The diversity of the issues will be covered from algorithms, mathematical models, and software engineering, by design methodologies and technical or practical solutions. This book intends to provide the reader with a comprehensive overview of the current state of the art, case studies, hardware and software solutions, analytics, and data science in dependability engineering.